Laparoscopic treatment of ectopic pregnancy in cesarean section uterine scar: report of a case - Ramírez C, Juan (2015)
Ectopic pregnancy is a gestation that nests outside of the uterus endometrial lining. Incidence is estimated at 0.94-2.6% of all pregnancies. Its location in a previous cesarean section uterine scar is a rare (0.15%) presentation of this disease, accounting for 6.15% of ectopic pregnancy cases occurring in women with previous cesarean section. A case of a 28 year-old woman G: 5 P: 0412, with history of 3 cesarean sections was hospitalized in Hospital Nacional Docente Materno Infantil (HONADOMANI) San Bartolomé in February 2013 because of transvaginal ultrasound diagnosis of ectopic pregnancy located in previous uterine cesarean scar; it was successfully resolved by laparoscopic management. Cases of ectopic pregnancy located in the uterine scar from previous cesarean are increasing due to the rising cesarean section rate. Transvaginal ultrasonography is crucial for diagnosis. There is no current consensus or guidelines for its management.